Epistemic and Deontic Modalities in English and Arabic:A Contrastive Study (Journal of the College of Basic Education, 2022)
Modality is the category of meaning used to talk about possibilities andnecessities, essentially, states of affairs beyond the actual.The present study aims at:1-Describing epistemic and deontic modality in both languages, i.e. standard English and standard Arabic to identify the point similarities and differences between them in relation to this respect.2-Helping foreign learners of modern standard Arabic to obtain some knowledge of the models of expressing modality in Arabic.3-facilitating the task of the students of English –Arabic translation insofar as modality concerned .The analysis of the study has revealed the following point